Inadequacies in the conventional treatment of the radiation field of moving sources - Ardavan, H; Ardavan, A; Singleton, J; Fasel, J; Schmidt, A (2009)
There is a fundamental difference between the classical expression for the retarded electromagnetic potential and the corresponding retarded solution of the wave equation that governs the electromagnetic field. While the boundary contribution to the retarded solution for the potential can always be rendered equal to zero by means of a gauge transformation that preserves the Lorenz condition, the boundary contribution to the retarded solution of the wave equation governing the field may be neglected only if it diminishes with distance faster than the contribution of the source density in the far zone. In the case of a source whose distribution pattern both rotates and travels faster than light in vacuo, as realized in recent experiments, the boundary term in the retarded solution governing the field is by a factor of the order of R1/2 larger than the source term of this solution in the limit that the distance R of the boundary from the source tends to infinity. This result is consistent with the prediction of the retarded potential that part of the radiation field generated by a rotating superluminal source decays as R-1/2, instead of R-1, a prediction that is confirmed experimentally. More importantly, it pinpoints the reason why an argument based on a solution of the wave equation governing the field in which the boundary term is neglected (such as appears in the published literature) misses the nonspherical decay of the field. © 2009 American Institute of Physics.